How to Glow and Stay Fresh: Some Advice on Deodorants Penned by Aetius of Amida - Kokoszko, Maciej; Rzeźnicka, Zofia (Studia Ceranea, 2023)
As far as women’s wellbeing is concerned, ancient and Byzantine physicians took great care not only of their patients’ health sensu stricto but also of their appearance. A testimony of the approach is given, for instance, by Aetius of Amida’s (6th cent. AD) Libri medicinales, where he devotes much attention to cosmetics, including a group of deodorising antiperspirants called καταπάσματα. In our study we analyse one prescription, taken by Aetius from Criton of Heraclea’s (1st/2nd cent. AD) treatise, trying to prove that it is very informative of medical (especially pharmaceutical) theory as well as practice in the social context of the 6th century AD. In order to achieve our goal, first, we analyse ancient and Byzantine materia medica, scrutinizing the medical properties ascribed to each component of the cosmetic in the light of the theory in force between the 1st and the 6th centuries AD. Next, we determine the method of preparation of the antiperspirant, its form, the mode and place of its application. Finally, we proceed to assess its market value as a marker exposing the group of the cosmetic’s addressees. As a result, we conclude that the recipe was competently worked out on the basis of a theory commonly accepted by medical authorities, and that the preparation was designed for women (but also for men) of a high social status.